Sustainable Development and Renewable Energy Sectors: Selected Indicators in European Union and Poland - Anna Klepacka (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The aim of this article was to show the position of Poland in the renewable energy subsectors among the European Union countries. The research covered the areas of biomass, solar heating and heat pumps, showing the degree of their utilization, power required to drive the system and their production in 2016. The provided information was supplemented with a revenues per employee in thousand euros in chosen subsectors of renewable energy sources in the year 2016. The main tool for carrying out the set objective was the use of descriptive and comparative methods. The results of the survey demonstrated Poland’s prominent place in the sector of liquid biofuels (1st place in EU), thanks to the significant supply of raw materials as well as development perspectives in solar energy, which is confirmed by the world's statistics indicating a record number of photovoltaic installations fitted (PV).